Before-after differences in labor market outcomes for participants in medical rehabilitation in Germany - Sebastian Fischer; Inna Petrunyk; Christian Pfeifer; Anita Wiemer (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2014)
The authors address the issue of effectiveness of medical rehabilitation in terms of labor market outcomes by analyzing a large representative administrative panel data set for Germany. The research design focuses on socio-demographic group differences in before-after differences in days with unemployment benefits, days in employment, and labor income of participants in medical rehabilitation. The mean before-after differences indicate that medical rehabilitation is rather ineffective with respect to labor market outcomes, because the number of days with unemployment benefits is larger and the number of working days and labor income are smaller after the rehabilitation than before. The differences in the before-after differences are however large between socio-demographic groups. For example, older participants perform significantly worse and better educated participants have significant better labor market outcomes after the rehabilitation than before, whereas gender differences are small.
Keywords: I1; J2; 330; medical rehabilitation; effectiveness; labor market performance